Evaluation of Hepatoprotective Activity of Vitex negundo Linn. against Paracetamol Induced Hepatotoxicity in Rats - Ladda, P. L.; Magdum, C. S.; Naikwade, N. S. (Current Aspects in Pharmaceutical Research and Development Vol. 8, 2022)
Objective: The present study was intended to evaluate the hepatoprotective activity of ethanolic extract of leaves of Vitex negundo Linn. The Vitex negundo Linn. is a medicinal plant found throughout India. It is a short plant of mediterranian region and used as herbal remedy of folklore usage. Methods: The ethanolic extract of Vitex. Negundo Linn. (300 mg/kg) was administered orally by suspending in tween-20 solution to the animals with hepatotoxicity induced by paracetamol (3 gm/kg). Silymarin (25 mg/kg) was given as reference standard. The hepatoprotective activity was also supported by histopathological studies of liver tissue. An effective significant alteration in all biochemical parameters and histopathological sections were observed Results: Since results of biochemical studies of blood samples of paracetamol treated rats showed significant increase in the levels of serum enzyme activities, reflected the liver injury caused by paracetamol and blood samples from the animals treated with the oral administration of ethanol extract produced a significant reduction in serum enzymes alanine aminotransferase (ALT), aspartate aminotransferase, (AST), alkaline phosphatase (ALP) to the acute hepatotoxic induced rats. They exhibited a significant inhibition of hepatic toxicity by using various marker enzymes and the histopathological analysis. Conclusion: From these results, it is concluded that the Vitex negundo Linn. is effective in protecting the liver against the injury induced by paracetamol in rats at the dose of 300 mg/kg/body weight. These results suggest that leaves of Vitex negundo Linn. may supports the hepatic cells protection.